2016
DOI: 10.1075/bct.87.05has
|View full text |Cite
|
Sign up to set email alerts
|

Discourse-structuring functions of initial adverbials in English and Norwegian news and fiction

Abstract: This chapter explores the discourse-structuring functions of initial adverbial adjuncts in English and Norwegian news and fiction. Such discourse functions have to do with discourse linking and information management. The corpus study reveals frequency differences in the use of initial adjuncts across the languages, which are to some extent connected with an overall greater frequency of adjuncts in Norwegian. While initial adjuncts in fiction often signal cohesive relations, those in news are more typically du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 11 publications
2
14
0
Order By: Relevance
“…She investigates 14 texts within genres like "textbooks", "academic papers" and "the modern novel", and illustrates that different text types make use of different themes, but without formulating any clear-cut distinctions between different text types. Further support for the claim that text type influences thematic structure can be found in a study of initial adjuncts in news and fiction (Hasselgård, 2014), where it is shown that these two genres differ both as regards the frequency of initial adjuncts, which are more common in fiction than in news, and in the meanings expressed by them, with the most prominent difference being that initial adjuncts expressing 'time' are more frequent in fiction than in news.…”
Section: Previous Research On Thematic Structurementioning
confidence: 74%
See 4 more Smart Citations
“…She investigates 14 texts within genres like "textbooks", "academic papers" and "the modern novel", and illustrates that different text types make use of different themes, but without formulating any clear-cut distinctions between different text types. Further support for the claim that text type influences thematic structure can be found in a study of initial adjuncts in news and fiction (Hasselgård, 2014), where it is shown that these two genres differ both as regards the frequency of initial adjuncts, which are more common in fiction than in news, and in the meanings expressed by them, with the most prominent difference being that initial adjuncts expressing 'time' are more frequent in fiction than in news.…”
Section: Previous Research On Thematic Structurementioning
confidence: 74%
“…But here it is clear that Norwegian L2 writers of English have adapted better to English discourse conventions than the Danish L2 writers investigated by Shaw, and indeed the present L2 writers have managed to comply with English discourse conventions despite the cross-linguistic difference resulting from the lower frequency of marked themes functioning as Adjuncts in L1Nor. Hasselgård (2014) found more initial adjuncts in Norwegian than in English, in both news and fiction, which indicates that the text-type or genre also affects the use of marked themes functioning as Adjunct.…”
Section: 2mentioning
confidence: 99%
See 3 more Smart Citations